Biotechniques used in native forest species - Abedini, W.; Boeri, P.; Marinucci, L.; Ruscitti, M.; Scelzo, L. (Forest Systems, 2000)
The «talares» are a native wooded community of Buenos Aires province (Argentine). They are be coming extined due to the agricultural frontier expansion, the urbanization and seed regeneration problems. The most important forest species that constitute them are: Celtis tala Gill. ex Planch. (tala), Acacia caven (Mol.) Mol. (espinillo), Parkinsonia aculeata L. (cina-cina) and Erythrina crista-galli L. (seibo). The aim of this work is the adjustment of a protocol for the micropropagation in vitro, through the adventitious organogenesis from the young material of this native forest species. As explant it was used sections of seedling obtained from seeds germinated in vitro, wich were prepared and desinfected for his cultivation. The basal medium more appropiated was the Broadleaved Tree Medium (BTM) (Chalupa, 1983), complemented with different growth regulators. It was obtained calli, roots and buds. Whole plants regenerated are in the aclimated stage.